2006
DOI: 10.1021/ma060841b
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization in Nitroxide-Mediated Radical Polymerization in Dispersed Systems

Abstract: Modified Smith-Ewart equations were used to quantitatively investigate compartmentalization effects in nitroxide-mediated radical polymerization in dispersed systems. Calculations were carried out for the specific system 2,2,6,6-tetramethylpiperidinyl-1-oxy (TEMPO)/styrene at 125 °C with thermal initiation included in the model, and accounting for compartmentalization of both propagating radicals and nitroxide. For particles with diameter (d) less than approximately 60 nm, a reduction in particle size led to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
303
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(329 citation statements)
references
References 46 publications
22
303
4
Order By: Relevance
“…Such cases are found when k 2 /k t is small, i.e., in a bad living condition [14]. Because the bimolecular termination is significant in bulk polymerization in such cases, the segregation of radicals into different polymer particles [6] reduces the termination frequency. Reduced termination frequency slows down the accumulation of the trapping agents in a particle.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Such cases are found when k 2 /k t is small, i.e., in a bad living condition [14]. Because the bimolecular termination is significant in bulk polymerization in such cases, the segregation of radicals into different polymer particles [6] reduces the termination frequency. Reduced termination frequency slows down the accumulation of the trapping agents in a particle.…”
Section: Figure 12mentioning
confidence: 99%
“…For SRMP and ATRP, theoretical calculation results have shown that a particle size region may exist in which the polymerization rate is larger than bulk polymerization [6][7][8][9][10][11][12][13][14], which was named the acceleration window [10]. Figure 2 shows a typical example.…”
Section: Introductionmentioning
confidence: 99%
“…Compartmentalization is an intrinsic feature of polymerization in dispersed systems [16], and it affects the polymerization in two ways: a segregation effect and a confined space effect [73]. The former effect refers to a fact that two radicals located in separate particles cannot react together, i.e., a termination rate is decreased.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…Recent modeling results show that significant compartmentalization effect requires a small particle size [73]. However, experimental evidence of compartmentalization effect on CRPs in aqueous dispersed media is still not clear [74].…”
Section: Compartmentalizationmentioning
confidence: 99%
“…Radical polymerization in heterogeneous systems is more complex than homogeneous systems due to various mechanistic aspects, e.g., entry/exit events and compartmentalization, 30 as well as aspects related to colloidal stability. For example, the extent of nitroxide partitioning to the continuous phase may affect NMP in heterogeneous systems, 31 and for sufficiently small particles, the deactivation rate may increase due to the confined space effect 32,33 (deactivation of a propagating radical occurring rapidly in a confined space). These intrinsic features of heterogeneous systems can ideally be exploited-for example, it is in some cases possible to improve the control/livingness in NMP and ATRP 34,35 by exploiting the confined space effect on deactivation by use of sufficiently small particles.…”
Section: Controlled/living Radical Polymerizationmentioning
confidence: 99%